The Nature of Noradrenergic Volume Transmission From Locus Coeruleus to Brainstem Mesencephalic Trigeminal Sensory Neurons - Toyoda, Hiroki; Won, Jonghwa; Kim, Wheedong; Kim, Hayun; Davy, Oscar; Saito, Mitsuru; Kim, Doyun; Tanaka, Takuma; Kang, Youngnam; Oh, Seog Bae (Frontiers in Cellular Neuroscience, 2022)
Noradrenergic neurons in the locus coeruleus (LC) release noradrenaline that acts via volume transmission to activate extrasynaptic G-protein coupled receptors (GPCRs) in target cells throughout the brain. As the closest projection, the dorsal LC laterally adjoins the mesencephalic trigeminal nucleus (MTN), in which proprioceptive primary sensory neurons innervating muscle spindles of jaw-closing muscles are exceptionally located. MTN neurons express α2-adrenergic receptors (α2-ARs) and display hyperpolarization-activated cyclic nucleotide-gated (HCN) current (Ih), which is downregulated by α2-AR activation. To quantify the activity-dependent outcome of volume transmission of noradrenaline (NA) from LC to MTN, we investigated how direct LC activation inhibits Ih in MTN neurons by performing dual whole-cell recordings from LC and MTN neurons. Repetition of 20 Hz spike-train evoked with 1-sec current-pulse in LC neurons every 30 sec resulted in a gradual decrease in Ih evoked every 30 sec, revealing a Hill-type relationship between the number of spike-trains in LC neurons and the degree of Ih inhibition in MTN neurons. On the other hand, when microstimulation was applied in LC every 30 sec, an LC neuron repeatedly displayed a transient higher-frequency firing followed by a tonic firing at 5–10 Hz for 30 sec. This subsequently caused a similar Hill-type inhibition of Ih in the simultaneously recorded MTN neuron but with a smaller Hill coefficient, suggesting a lower signal transduction efficacy. In contrast, 20 Hz activity induced by a 1-sec pulse applied every 5–10 sec caused only a transient facilitation of Ih inhibition followed by a forced termination of Ih inhibition. Thus, the three modes of LC activities modulated the volume transmission to activate α2-adrenergic GPCR to differentially inhibit Ih in MTN neurons.